Polymerized nano-curcumin attenuates neurological symptoms in EAE model of multiple sclerosis through down regulation of inflammatory and oxidative processes and enhancing neuroprotection and myelin repair. (December 2015) - Mohajeri, Maryam; Sadeghizadeh, Majid; Najafi, Farhood; Javan, Mohammad
Abstract: Multiple Sclerosis (MS) is an inflammatory demyelinating disorder of central nervous system (CNS). Polyphenol curcumin has been used in traditional medicine as an effective drug for a variety of diseases. Different formulations of curcumin are introduced to increase its stability and effectiveness. Here we have examined the effect of polymerized form of nano-curcumin (PNC) on experimental autoimmune encephalomyelitis (EAE) as an animal model of MS. EAE was induced in female Lewis rats and PNC or curcumin was daily administrated intraperitonealy from day 12–29 post immunization. When the prophylactic effect of PNC was under investigation, rats received PNC from the first day of immunization. Treatment with PNC resulted in decreased scores of disease in therapeutic and prophylactic administration when compared with control group. Staining by luxol fast blue and H&E and immuno-staining of lumbar spinal cord cross sections, confirmed a significant decrease in the amounts of demyelination, inflammation and BBB breaking down. Gene expression studies in lumbar spinal cord showed a corrected balance of pro-inflammatory and anti-inflammatory genes expression, decreased oxidative stress, improved remyelination and increased progenitor cell markers after treatment with PNC. Our results demonstrated an efficient therapeutic effect of PNC as an anti-inflammatory and anti-oxidative stress agent, with significant effects on the EAE scores and myelin repair mechanisms. Highlights: Curcumin was prepared as a polymerized Nano-formulation to increase its bioavailability. Polymerized nano-curcumin (PNC) reduced the EAE symptoms. PNC reversed EAE-induced changes in the expression of pro-inflammatory, anti-inflammatory and oxidative stress marker genes. PNC improved remyelination and increased progenitor cell markers in spinal cord of EAE rats.